Pregnant Women Presented with Acute Kidney Injury: A Case Report - Choudhury, Farzana Rabee (Journal of Current and Advance Medical Research, 2015)
Acute Renal Failure is most challenging clinical problem when it occurs during pregnancy. Septic abortion is the most common cause of PRAKI in developing countries but its worldwide incidence has declined significantly. Sometimes septic abortion complicated by multiorgan failure. This 35 yrs multiparous lady having history of induced abortion, presented with multiorgan dysfunction. The patient was successfully treated and discharged with total care. Journal of Current and Advance Medical Research, 2015;2(2):47-48